ANTESEDEN DAN KONSEKUENSI DARI ATTITUDE TOWARD MOBILE BANKING APPLICATION - Damayanti, Sisca; Luki Adiati Pratomo; Firdayeti; Dyah Astarini; Khairunnisa; Wardah Islami (Media Ekonomi, 2024)
This study discusses the antecedents and consequences of attitudes toward using mobile banking among the current generation. The research design employed is hypothesis testing, with data collected using a non-probability sampling method through purposive sampling, targeting respondents who are mobile banking users. The data is analyzed using Structural Equation Modeling (SEM), preceded by prerequisite tests for validity and reliability. The hypothesis testing results reveal that out of nine proposed hypotheses, four are not supported.